The pharmacokinetics of levobupivacaine 0.5% after infraorbital or inferior alveolar block in anesthetized dogs - Pavlica, Matic; Kržan, Mojca; Nemec, Ana; Kosjek, Tina; Baš, Anže; Seliškar, Alenka (Frontiers in Veterinary Science, 2022)
Data are lacking on the pharmacokinetic profile and safety of levobupivacaine (LB) used for regional anesthesia of the maxilla and mandibles in dogs. Infraorbital block (n=10), inferior alveolar block (n=10) or both infraorbital and inferior alveolar blocks (n=10) were administered to dogs undergoing dental surgery under isoflurane anesthesia. The dose of LB was calculated as 0.11 mL/kg2/3 for the infraorbital block and 0.18 mL/kg2/3 for the inferior alveolar block. Blood samples were collected before and immediately after administration of the oral blocks, and 3, 4, 7, 12, 17, 32, 47, 62, 92, and 122 minutes thereafter. Quantification of LB in plasma was performed by LC-MS /MS. The results are presented as median and interquartile range. In dogs in which all four quadrants of the oral cavity were desensitized with LB, the Cmax was 1335 (1030–1929) ng/mL, the Tmax was 7 (4.75–14.5) minutes, and the AUC(0→120) was 57976 (44954–96224) ng minute/mL. Plasma concentrations of LB were several times lower than the reported toxic concentrations, and no signs of cardiovascular depression or neurotoxicity were observed in any of the dogs, suggesting that the occurrence of severe adverse effects after administration of LB at the doses used in this study is unlikely.